2020
DOI: 10.1155/2020/8850594
|View full text |Cite
|
Sign up to set email alerts
|

Educational Intervention Improved Parental Knowledge, Attitudes, and Practices (KAP) and Adherence of Patients with Celiac Disease to Gluten-Free Diet

Abstract: Background. Raising the knowledge level though education for a celiac disease patient’s parents could improve the parent’s adherence and practice and consequently recover the patient’s adherence and symptoms and increase the patient’s compliance. Aim. The present study was aimed at assessing the knowledge, attitudes, and practices (KAP) of parents who have children with celiac disease aged from 2 to 15 years old and the change in self-reported patient’s adherence pre-/posteducational intervention. Method. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
10
1
1
Order By: Relevance
“…Parents were asked to complete a validated questionnaire pre and postintervention. Self‐reported patient's adherence between pre‐ and posteducational intervention showed a significant improvement in all variables 114 …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Parents were asked to complete a validated questionnaire pre and postintervention. Self‐reported patient's adherence between pre‐ and posteducational intervention showed a significant improvement in all variables 114 …”
Section: Resultsmentioning
confidence: 94%
“…Self-reported patient's adherence between pre-and posteducational intervention showed a significant improvement in all variables. 114…”
Section: Whymentioning
confidence: 99%
“…3 Other studies have looked at different formats and the efficacy of GFD education in both pediatric and adult patients. Elsahoryi et al 4 studied education sessions for parents with children who have CeD. These included a RD and were held as in-person, large group sessions with 20 parents in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly another study in Lahore, found that 44% mothers used healthy complementary foods, and 30% of them used mixture of home-prepared and commercially made foods, whereas, 16% preferred only readymade food. 14,18…”
Section: Discussionmentioning
confidence: 99%